(untitled) (Central Medical College Journal, 2022)
Cardiac troponin I is a highly sensitive and specific marker of myocardial necrosis. In addition to the strong diagnostic role of cardiac troponin I its prognostic value has become increasingly well established for patients presenting with acute coronary syndrome. However, there have been conflicting reports on the value of troponin in the setting of PCI is stable and unstable coronary disease. Objective: To assess the role of cardiac troponin I in predicting outcome after PCI. Methods and results: CTnl was measured immediately before and at 8 hrs and at chest pain after PCI in 80 consecutive patients with stable coronary artery disease. Twenty of them with post procedural CTnl level 50.4 ng/ml were excluded because of the inability to do repeat estimation of CTnl at chest pain. Among the rest sixty patients, thirty had post procedural troponin <0.4 ng/ml were considered as group I and thirty had post procedural rise of CTnI >0.4 ng/ml were considered as group II. CTnl level, 0.4 ng/ml was consider as cut off value for grouping patients was based on ACC/ AHA/ ISCAI 2005 guide line definition of peri procedural myocardial infarction. The study end point was the following adverse cardiac events-recurrent angina, cardiogenic shock, significant arrythmias, congestive heart failure, Q wave MI, repeat PCI/ CABG, death during hospital stay and at 30 days follow up. In this study base line parameters like age, sex, BMI, risk factors, anginal class, base line ECG and LVEF showed no statistically significant difference between the two groups. Angiographic parameters such as types of lesion and procedural complications shows statistically significant difference between two groups. In-hospital adverse cardiac events after the procedure was significantly higher in group II than group 1 (P<0.01). The mean duration of post procedural hospital stay was also significantly higher in group II than group 1 (P<0.01). At 30 days follow up there has no incremental risk of adverse cardiac events. Conclusion: CTnl rise at peri procedural myocardial infarction level was observed in 37.5% of this study patient. This level of CTnl was significantly predictive of an increased risk of adverse cardiac events at hospital follow up. Central Medical College Journal Vol 5 No 2 Jul 2021 PP 106-115